(untitled) (Global Journal of Human-Social Science, 2021)
This research examines the causal relationship between social conflicts and Value-Added Tax (VAT) in Mozambique. The study tests two hypotheses; the "tax-burden" hypothesis which is used to evaluate the long-run relationship, and the "tax-conflicts" hypothesis which estimates the short-run relationship between VAT and social conflicts. Vector Error Correction Model (VECM) is used to examine this relationship. The data used comprise the period from 1994 to 2018. The outcomes of the study suggest that the prices of goods and services included in the new VAT system had a causal relationship with social conflicts in the short-run in Mozambique; these results support the "tax-conflicts" hypothesis. Under this hypothesis, the unsustainable tax imbalances can be mitigated by exempting or reducing the VAT of some indispensable consumption goods and services. The VECM results of long-run causal relationships suggest a bidirectional causality between VAT and social conflicts, supporting the "taxburden" hypothesis. Under this hypothesis our finding suggests that in the long-run Mozambique’s central government should design a new VAT system; expand and diversify the sources of revenue.